The effects of forest residue management on topsoil nutrient dynamics, and on early growth responses of Eucalyptus grandis x urophylla under varied levels of fertilization - Nieto Lawrence, Juan Sebastian (Stellenbosch : Stellenbosch University, 2022)
Thesis (MSc) -- Stellenbosch University, 2022.